Open tibia/fibula in the elderly: A retrospective cohort study. (March 2022) - Lee, Alice; Geoghegan, Luke; Nolan, Grant; Cooper, Kerri; Super, Jonathan; Pearse, Michael; Naique, Satyajit; Hettiaratchy, Shehan; Jain, Abhilash
Abstract: The incidence of open tibia/fibula fractures in the elderly is increasing, but current national guidelines focus on the aggressive treatment of high-energy injuries in younger patients. There is conflicting evidence regarding whether older age affects treatment provision and outcomes in open fractures. The aim of this study was to determine if elderly patients are sustaining a different injury to younger patients and how their treatment and outcomes differ. This may have implications for future guidelines and verify their application in the elderly. In this retrospective single centre cohort study (December 2015–July 2018), we compared the injury characteristics, operative management and outcomes of elderly (≥65 years) and younger (18–65 years) patients with open tibia/fibula fractures. An extended cohort examined free flap reconstruction. In total, 157 patients were included. High-energy injuries were commoner in younger patients (88% vs 37%; p<0.001). Most were Gustilo-Anderson IIIb in both age groups. Elderly patients waited longer until debridement (21:19 vs 19:00 h) and had longer inpatient stays (23 vs 15 days). There was no difference in time to antibiotics, operative approach or post-operative complications. Despite the low-energy nature of elderly patients' injuries, the severity of soft tissue insult was equivalent to younger patients with high-energy injuries. Our data suggest that age and co-morbidities should not prohibit lower limb reconstruction. The current application of generic guidelines appears suitable in the elderly, particularly in the acute management. We suggest current management pathways and targets be reviewed to reflect the greater need for peri-operative optimisation and rehabilitation in elderly patients.